Canadian Consensus Guidelines for the Management of Cytomegalovirus Disease in HIV/AIDS. Issue 6 (1st December 2004) - Lalonde, Richard G; Bovivin, Guy; Deschênes, Jean; Hodge, William G; Hopkins, J Jill; Klein, Alex H; Lindley, Janette I; Phillips, Peter; Shafran, Stephen D; Walmsley, Sharon
Abstract : BACKGROUND: The management of HIV-infected patients with cytomegalovirus (CMV) disease has changed significantly with the availability of highly active antiretroviral therapy (HAART). OBJECTIVES: These updated guidelines are intended to provide practical help to physicians managing HIV-positive patients with or at risk for CMV disease. METHODS: The 10 members of the Canadian CMV Disease in HIV/AIDS Consensus Group were infectious disease specialists, a primary care physician and ophthalmologists with expertise in HIV and CMV infection. Financial support by Hoffmann-La Roche Canada Ltd was unrestricted, and was limited to travel expenses and honoraria. The consensus group met in June and October 2002. Key areas to be considered were identified, and group members selected, reviewed and presented relevant recent literature for their assigned section for the group's consideration. Evidence was assessed based on established criteria, which were expert opinions of the members. Draft documents were circulated to the entire group and modified until consensus was reached. The final guidelines represent the group's consensus agreement. The guidelines were approved by the Canadian Infectious Disease Society. RESULTS AND CONCLUSIONS: The guidelines address symptom monitoring, screening for early detection and prevention, and treatment using oral, intravenous and intraocular anti-CMV therapies in conjunction with HAART.